Migrant’s access to preventive health services in five EU countries - Rosano, Aldo; Dauvrin, Marie; Buttigieg, Sandra C.; Ronda, Elena; Tafforeau, Jean; Dias, Sonia (BMC health services research, 2017)
Background Preventive health services (PHSs) form part of primary healthcare with the aim of screening to prevent disease. Migrants show significant differences in lifestyle, health beliefs and risk factors compared with the native populations. This can have a significant impact on migrants’ access to health systems and participation in prevention programmes. Even in countries with widely accessible healthcare systems, migrants’ access to PHSs may be difficult. The aim of the study was to compare access to preventive health services between migrants and native populations in five European Union (EU) countries. Methods Information from Health Interview Surveys of Belgium, Italy, Malta, Portugal and Spain were used to analyse access to mammography, Pap smear tests, colorectal cancer screening and flu vaccination among migrants. The comparative risk of not accessing PHSs was calculated using a mixed-effects multilevel model, adjusting for potential confounding factors (sex, education and the presence of disability). Migrant status was defined according to citizenship, with a distinction made between EU and non-EU countries. Results Migrants, in particular those from non-EU countries, were found to have poorer access to PHSs. The overall risk of not reporting a screening test or a flu vaccination ranged from a minimum of 1.8 times (colorectal cancer screening), to a high of 4.4 times (flu vaccination) for migrants. The comparison among the five EU countries included in the study showed similarities, with particularly limited access recorded in Italy and in Belgium for non-EU migrants. Conclusions The findings of this study are in accordance with evidence from the scientific literature. Poor organization of health services, in Italy, and lack of targeted health policies in Belgium may explain these findings. PHSs should be responsive to patient diversity, probably more so than other health services. There is a need for diversity-oriented, migrant-sensitive prevention. Policies oriented to removing impediments to migrants’ access to preventive interventions are crucial, to encourage more positive action for those facing the risk of intersectional discrimination.